Therapeutic exercises for the control of temporomandibular disorders - Alberto da Rocha Moraes; Monique Lalue Sanches; Eduardo Cotecchia Ribeiro; Antonio Sérgio Guimarães (Dental Press Editora, 2013)
INTRODUCTION: Temporomandibular disorder (TMD) is a multifactorial disease. For this reason, it is difficult to obtain an accurate and correct diagnosis. In this context, conservative treatments, including therapeutic exercises classified as stretching, relaxation, coordination, strengthening and endurance, are oftentimes prescribed. OBJECTIVE: Thus, the aim of the present article was to conduct a literature review concerning the types of exercises available and the efficacy for the treatment of muscular TMD. METHODS: The review included researches carried out between 2000 and 2010, indexed on Web of Science, PubMed, LILACS and BBO. Moreover, the following keywords were used: Exercise, physical therapy, facial pain, myofascial pain syndrome, and temporomandibular joint dysfunction syndrome. Studies that did not consider the subject "TMD and exercises", used post-surgery exercises and did not use validated criteria for the diagnosis of TMD (RDC/TMD) were not included. RESULTS: The results comprised seven articles which proved therapeutic exercises to be effective for the treatment of muscular TMD. However, these studies are seen as limited, since therapeutic exercises were not applied alone, but in association with other conservative procedures. In addition, they present some drawbacks such as: Small samples, lack of control group and no detailed exercise description which should have included intensity, repetition, frequency and duration. CONCLUSION: Although therapeutic exercises are considered effective in the management of muscular TMD, the development of randomized clinical trials is necessary, since many existing studies are still based on the clinical experience of professionals.